Development of Guided Inquiry-Based Chemistry Modules and Insight of Islamic-Science Integration in Chemical Bonding Materials in Iain Kerinci - Betaria Putra (al-fikrah: Jurnal Manajemen Pendidikan, 2022)
The use of Islamic-Science-based teaching materials in the lecture process is an alternative that can be done in order to instill religious values in students. In addition to obtaining material from certain courses, students will get Islamic discourse which is full of moral messages. So that it is expected to motivate students to be more enthusiastic about learning. Another benefit of developing teaching materials based on the integration of Islam-Science is that students can analyze an object of Science from an Islamic perspective as done by Islamic scientists. Guided Inquiry is a strategy that can build student understanding based on prior knowledge, following a learning cycle in the form of orientation, exploration, concept formation, application, and closing, discussing and interacting with other people. Development, Test Subjects, Types of Data, Data Collecting Instruments, Analysis Techniques for Chemical Bonding Test Items.